THE CORRELATION BETWEEN STUDENTS’ SPEAKING ANXIETY AND THEIRORAL PROFICIENCY - Reinasya Br Surbakti; Nazwa Umri Damanik; Izzati Amirah Sari; M Rafli Raja Gazali Nahulae (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2026)
ABSTRACT This study aimed to examine the relationship between speaking anxiety and English oral proficiency among EFL students. A quantitative approach with a correlational design was employed. The sample consisted of 60 students from the Department of English Education, Faculty of Tarbiyah and Teacher Training, State Islamic University of North Sumatera (UIN-SU), selected using purposive sampling. Data were collected using the Foreign Language Classroom Anxiety Scale (FLCAS) and an oral proficiency test based on the IELTS Speaking Band Descriptors, and were analyzed using the Pearson Product Moment correlation. The results revealed a strong and statistically significant negative correlation between speaking anxiety and English oral proficiency (r = –0.673, p < 0.001). The coefficient of determination (r² = 0.453) indicated that 45.3% of the variance in oral proficiency was associated with speaking anxiety, while the remaining variance was likely related to other factors. These findings suggest that students with higher levels of speaking anxiety tend to demonstrate lower oral English proficiency. Therefore, English language instruction should incorporate strategies that reduce speaking anxiety while fostering a supportive learning environment to enhance students' oral communication competence. ABSTRAK Penelitian ini bertujuan untuk menganalisis hubungan antara kecemasan berbicara dan kemahiran berbicara bahasa Inggris pada mahasiswa EFL. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional. Sampel penelitian terdiri atas 60 mahasiswa Program Studi Pendidikan Bahasa Inggris, Fakultas Tarbiyah dan Keguruan, Universitas Islam Negeri Sumatera Utara (UIN-SU), yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui Foreign Language Classroom Anxiety Scale (FLCAS) dan tes kemahiran berbicara menggunakan IELTS Speaking Band Descriptors, kemudian dianalisis dengan uji korelasi Pearson Product Moment. Hasil penelitian menunjukkan adanya hubungan negatif yang kuat dan signifikan antara kecemasan berbicara dan kemahiran berbicara bahasa Inggris (r = –0.673; p < 0.001). Nilai r² = 0.453 menunjukkan bahwa 45,3% variasi kemahiran berbicara berhubungan dengan tingkat kecemasan berbicara, sedangkan sisanya kemungkinan dipengaruhi oleh faktor lain. Temuan ini menunjukkan bahwa mahasiswa dengan tingkat kecemasan berbicara yang lebih tinggi cenderung memiliki kemampuan berbicara yang lebih rendah. Oleh karena itu, pembelajaran bahasa Inggris perlu menerapkan strategi yang mampu mengurangi kecemasan berbicara sekaligus menciptakan lingkungan belajar yang mendukung perkembangan kompetensi komunikasi lisan.